Bone tissue engineering scaffold

By using hollow grid-shaped stents to fill porous zinc-based metal spheres and β-TCP particles in bone tissue engineering scaffolds, the problem of insufficient mechanical properties of traditional scaffolds is solved, and the scaffold provides mechanical support in the early stage and promotes new bone formation, meeting the repair needs of large segments of bone defects.

CN109938896BActive Publication Date: 2025-03-07SHANGHAI NINTH PEOPLES HOSPITAL SHANGHAI JIAO TONG UNIV SCHOOL OF MEDICINE
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN201910316934.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2019-04-19
Publication Date
2025-03-07
Estimated Expiration
2039-04-19

AI Technical Summary

Technical Problem

Existing bone tissue engineering stents are difficult to meet the mechanical properties requirements in the repair of large segments of bone defects. At the same time, traditional inert metal materials have problems such as stress occlusion effect, thrombosis and uneven degradation.

Method used

The porous zinc-based metal balls were filled with hollow grid-like scaffolds, combined with β-TCP particles, and porous zinc-based metal balls were prepared by laser cautery to promote the growth of bone cells and the release of zinc ions, and improve the mechanical properties and biocompatibility of the scaffolds.

Benefits of technology

The stent provides good mechanical support in the early stage, and gradually reduces zinc ions to promote new bone formation, significantly improves the mechanical properties and biological functions of bone repair, and meets the repair needs of large segments of bone defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN109938896B_ABST
    Figure CN109938896B_ABST
Patent Text Reader

Abstract

The present invention discloses a bone tissue engineering scaffold, including a hollow grid-shaped scaffold and a porous zinc-based metal ball filled therein, the porous zinc-based metal ball can be a solid ball with holes and grooves on the surface or a fluffy ball rolled by metal wire; an internal support column can also be arranged in the scaffold to provide more mechanical properties; β-TCP particles can be filled to enrich bone marrow mesenchymal stem cells. The present invention combines a grid scaffold prepared by titanium or zinc-based metal and its internal support column to prepare a bone tissue engineering scaffold with excellent mechanical properties, wherein the porous zinc-based metal ball can promote osteogenic differentiation and inhibit osteoclast differentiation, while providing support, promote the regeneration and ingrowth of bone tissue, and then gradually be replaced by bone tissue during the degradation process, and β-TCP particles can enrich mesenchymal stem cells and promote bone repair. The present invention can be applied to large bone defects in load-bearing parts, promote bone tissue regeneration on the basis of mechanical support, and achieve the therapeutic effect of repairing large bone defects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of medical biomaterials and relates to a bone tissue engineering scaffold, in particular to a degradable bone tissue engineering scaffold capable of promoting bone repair. Background Art

[0002] Medical inert metal materials represented by stainless steel, titanium alloy, cobalt-based alloy, and nickel-titanium shape memory alloy are the earliest medical materials used in the human body. Due to their high strength, fatigue resistance, easy processing and molding, stable in vivo state, and good biocompatibility, they have become the most widely used type of medical biomaterials in clinical use. However, after centuries of use, people are not satisfied with the traditional properties of medical inert metal materials. Traditional medical inert materials also have some inherent defects, such as the stress shielding effect caused by the high elastic modulus of medical inert metal materials in orthopedic applications, and long-term complications of cardiovascular stents such as stent thrombosis and stent fracture. In addition, inert metal materials often contain harmful metal elements such as aluminum, cobalt, and chromium, which will increase the risk of allergic and inflammatory reactions if they remain in the body for a long time.

[0003] With the change of treatment concepts, people hope that medical implant materials can temporarily perform repair functions and remain in the body, while matching the repair process of tissues, and gradually degrade into degradation products that can be absorbed or excreted by the human body after completing their mechanical and biological functions, and finally be completely degraded and absorbed. Therefore, the emergence of degradable medical materials has set off a research boom.

[0004] In the field of bone tissue engineering, commonly used bone tissue repair materials include synthetic inorganic materials and polymer materials, as well as natural polymer materials. Commonly used synthetic inorganic materials include hydroxyapatite (HAP), β-tricalcium phosphate (β-TCP), bioactive glass (BG), calcium carbonate cement (CPC), etc.; as well as some polymer materials, such as polylactic acid (PLA), polyglycolic acid (PGA) and polylactic acid-glycolic acid copolymer (PLGA), etc.; natural polymer materials mainly include collagen, alginate, chitosan (CTS), etc. These materials have been widely used in clinical practice and have good biocompatibility and bioactivity, but due to their inherent mechanical strength defects, they often cannot meet the needs of repairing large bone defects.

[0005] β-tricalcium phosphate (β-TCP) has good biocompatibility and certain osteoinductivity, can enrich bone marrow mesenchymal stem cells and promote osteogenesis, repair bone defects, and has been widely used in clinical practice as a bone repair material. And the simple β-TCP mechanical properties are crossed, and the compressive strength is only about 2MPa, so it is difficult to be used to repair large bone defects in load-bearing parts. The Chinese patent document with publication number CN102764888A provides a titanium alloy human talus support rod of a composite porous β-TCP, which is a paste slurry prepared by injecting β-TCP and hydrogen peroxide and polyvinyl alcohol into a porous support rod made of titanium alloy, and is obtained after high temperature sintering. However, due to the low strength of β-TCP, the mechanical properties of the support rod are generally reduced, and the strength requirements of large bone defects to bone tissue scaffolds cannot be met.

[0006] Degradable metal materials have been widely studied due to their inherent mechanical strength advantages. Degradable metal materials mainly include degradable magnesium-based metals, degradable zinc-based metals and degradable iron-based metals. Among them, magnesium-based metals and iron-based metals have been widely studied. However, both types of materials have obvious shortcomings. For example, the degradation rate of magnesium-based metals in the human body environment is too fast and the degradation is uneven, which often leads to a rapid decrease in mechanical properties and is insufficient to provide sufficient fixation and support functions. In addition, the degradation of magnesium-based metals will produce a large amount of gas and cause local pH increases; while iron-based metals have a very slow degradation rate due to the protective effect of degradation products, causing problems similar to non-degradable metals. Therefore, researchers have tried a lot of methods to try to improve the degradation rate of magnesium-based metals and iron-based metals, but no perfect results have been achieved so far.

[0007] Compared with magnesium-based metals and iron-based metals, zinc-based metals have the following advantages: ① Since the standard electrode potential of Zn (-0.763V) is between Mg (-2.372V) and Fe (-0.447V), zinc and zinc alloys have a more suitable degradation rate. ② Zinc is an essential trace element for the human body. 90% of the zinc in the human body is stored in muscles and bones. It is one of the most important elements in protein synthesis and energy metabolism. It participates in a large number of physiological reactions such as human cell development and growth, gene expression, immune system and nervous system. This provides a basis for the good biocompatibility of zinc-based metals. ③ The degradation products of zinc-based metals are relatively stable compared with magnesium; after the degradation of zinc, its final products may be zinc oxide and zinc hydroxide, and the latter can further form soluble chloride salts in a high-chlorine environment, so in theory, no strong alkaline microenvironment and gas release are generated; ④ Zinc-based metals have good processing performance, low melting point, moderate chemical activity and mechanical processing performance, and are easy to cast and process.

[0008] Zinc is an essential element for the human body. 90% of zinc in the human body is stored in muscles and bones. It is one of the most important elements in protein synthesis and energy metabolism. It participates in a large number of physiological reactions such as human cell development and growth, gene expression, immune system and nervous system. It has a good effect on promoting osteogenesis and can enrich bone marrow mesenchymal stem cells. Zinc-based metals can gradually degrade and release zinc ions in the human body. Therefore, zinc-based metals with excellent mechanical strength and excellent osteogenesis can be used as ideal bone repair materials. A Chinese patent document with publication number CN103845762A discloses a method for preparing a porous bone scaffold by laser and adding zinc oxide to improve performance. However, it only adds a small amount of ZnO powder to the raw material of β-TCP to make a porous scaffold, and its effect on improving the mechanical properties of the scaffold is limited; and a Chinese patent document with publication number CN104258458A discloses a degradable open-porous porous zinc and zinc alloy biomaterial. Although it is mentioned that the material can be used as a new generation of degradable bone tissue engineering scaffold, the mechanical properties of the open-porous zinc material will be greatly affected; the above two tissue engineering scaffolds containing zinc-based metals are still difficult to meet the mechanical performance requirements of bone tissue scaffolds for large bone defects.

[0009] In addition, the biological functionality of zinc-based metals is also worthy of attention. Zn has been reported to promote osteoblastic differentiation and inhibit osteoclast differentiation. After being endowed with different alloy elements (such as Mg, Li, Cu, Ag, Ca, Sr, and Mn), its biological function of promoting osteoblasts and inhibiting osteoclasts can be further optimized, and bone defect repair materials can be prepared based on this. Summary of the invention

[0010] In view of the above problems existing in the prior art, the object of the present invention is to provide a degradable bone tissue scaffold which has high supporting strength and can promote the formation of new bone.

[0011] To achieve the above-mentioned object, the present invention provides a bone tissue engineering scaffold, comprising a hollow grid-shaped scaffold and porous zinc-based metal balls filled therein.

[0012] Furthermore, the hollow grid-shaped stent can be made of pure titanium or titanium alloy with excellent mechanical properties; but as needed, in other embodiments of the present invention, the stent can also be made of degradable zinc-based metal materials or other degradable metal materials, so that it can eventually be completely absorbed by the human body.

[0013] In order to be suitable for different application scenarios, the overall shape of the stent includes but is not limited to cylindrical, spherical, and many irregular shapes. In a preferred embodiment of the present invention, the overall shape of the stent is cylindrical, preferably with a diameter of 1-5 cm and a height of 2-10 cm.

[0014] Furthermore, the shape of the grid can be square, diamond, circular, elliptical, or any other feasible shape. The pore size of the grid is preferably 0.5-2 mm, and the size is suitable so that the filler in the stent will not fall out.

[0015] Preferably, the hollow grid-like bracket has internal support columns. The number of the internal support columns is preferably 3-5. The material of the support columns may be the same as or different from the material of the bracket outer shape, but should be a metal with excellent mechanical properties, such as titanium, titanium alloy, zinc or zinc alloy. In a cylindrical bracket, its internal support columns connect the top and bottom surfaces of the bracket; in a spherical bracket, at least one of its internal support columns passes through the center of the sphere, and the other support columns can connect any two points of the spherical surface in parallel or non-parallel. In a preferred embodiment of the present invention, the internal support columns are cylindrical with a diameter of 0.3-0.8mm, more preferably 0.4-0.6mm.

[0016] Furthermore, the porous zinc-based metal ball can be a porous solid ball or a porous fluffy ball.

[0017] In a preferred embodiment of the present invention, the porous zinc-based metal ball is a solid ball with a plurality of holes and grooves on the surface; preferably, the present invention adopts a laser ablation method to burn holes and grooves on the zinc-based metal solid ball. The purpose of providing the holes and grooves is to promote the growth of bone cells, increase the surface area of ​​the metal ball, and promote the release of zinc ions, thereby accelerating their degradation rate.

[0018] Furthermore, the particle size of the solid sphere with a plurality of holes and grooves on the surface is preferably 0.5-5 mm, the holes and grooves are circular, and the diameter thereof is preferably 0.1-0.3 mm, and the porosity is preferably 60%-90%.

[0019] In another preferred embodiment of the present invention, the porous zinc-based metal ball is a porous fluffy ball rolled from a degradable zinc-based metal wire, and the diameter of the metal wire is 0.1-0.3 mm; preferably, the preparation method is: first pull the zinc-based metal into a filament with a diameter of 0.1-0.3 mm, and then curl it into silk balls of different sizes. The purpose of rolling it into a silk ball is also to promote the growth of bone cells, increase the surface area of ​​the metal, promote the release of zinc ions, and accelerate its degradation rate. After the production is completed, the silk ball can be placed in the hollow grid-like bracket.

[0020] Furthermore, the particle size of the porous fluffy balls is preferably 2-8 mm.

[0021] The porous zinc-based metal spheres in the present invention do not need to be of the same size, and preferably have the following proportions:

[0022] Large particle size accounts for 30%-50%;

[0023] Medium particle size accounts for 20%-40%;

[0024] Small particle size accounts for 20%-40%.

[0025] For example, when the porous zinc-based metal ball is a porous solid ball, the large particle size is greater than 3.5 mm, the medium particle size is 1.0-3.5 mm, and the small particle size is less than 1.0 mm; or the large particle size is greater than 4 mm, the medium particle size is 2-4 mm, and the small particle size is less than 2 mm. When the porous zinc-based metal ball is a porous fluffy ball, the large particle size is greater than 5 mm, the medium particle size is 3-5 mm, and the small particle size is less than 3 mm.

[0026] The porous zinc-based metal spheres mixed in the above proportions can better exert their biological functions, bidirectionally regulate osteogenesis and osteoclastology, and promote the repair of bone defects.

[0027] Preferably, the hollow grid-shaped stent is also filled with β-TCP particles. The β-TCP particles can be commercially available or prepared by oneself, and the particle size of the β-TCP particles is preferably 0.5-5 mm, the porosity is preferably 60%-90%, and the pore size is less than 500 μm, preferably about 200 μm.

[0028] Preferably, the particle size distribution of the β-TCP particles also follows the following ratio:

[0029] Large particle size accounts for 30%-50%;

[0030] Medium particle size accounts for 20%-40%;

[0031] Small particle size accounts for 20%-40%;

[0032] Among them, the large particle size is greater than 3.5mm, the medium particle size is 1.0-3.5mm, and the small particle size is less than 1.0mm.

[0033] In a preferred embodiment of the present invention, the sizes and distribution ratios of the β-TCP particles and the porous zinc-based metal spheres follow the above distribution principle.

[0034] In a preferred embodiment of the present invention, the ratio of the number of the β-TCP particles to the number of the porous zinc-based metal spheres is 6:4-4:6. The porous β-TCP particles and the porous zinc-based metal spheres mixed in the above ratio can significantly improve the mechanical properties of the bone repair scaffold while maintaining the enrichment of bone marrow mesenchymal stem cells to promote bone repair.

[0035] Preferably, the zinc-based metal described in the present invention refers to pure zinc or a zinc alloy containing zinc in a mass fraction of more than 90%.

[0036] Furthermore, a single or multiple metal elements may be added to the above zinc alloy, and the addable elements include but are not limited to: magnesium Mg, copper Cu, silver Ag, lithium Li, manganese Mn, strontium Sr, calcium Ca, yttrium Y, gadolinium G, dysprosium Dy; wherein the mass fraction of each element in the alloy does not exceed 5%, and the total mass fraction of each element does not exceed 10%; further, the mass fraction of each of the silver, lithium, manganese, strontium, yttrium, gadolinium, and dysprosium elements does not exceed 1%, and more preferably does not exceed 0.6%.

[0037] We added alloying elements to pure zinc to prepare different zinc-based alloys and established a variety of degradable zinc-based alloy systems. While improving the mechanical properties of pure zinc, we further enhanced the osteogenic effect of zinc-based metals and the enrichment function of bone marrow mesenchymal stem cells. For example, by adding magnesium Mg, copper Cu, strontium Sr and other elements to pure zinc, we prepared binary zinc-magnesium, zinc-copper, zinc-strontium, and zinc-manganese alloy systems, all of which showed excellent osteogenic properties.

[0038] In a preferred embodiment of the present invention, the zinc alloy is a binary alloy, for example, a zinc-strontium binary alloy, wherein the mass fraction of strontium is 0.5%-2%, and more preferably 1%-1.5%; or a zinc-manganese binary alloy, wherein the mass fraction of manganese is 0.1-1.5%, and more preferably 0.3-1.2%; or a zinc-copper binary alloy, wherein the mass fraction of copper is 1-3%, and more preferably 1.5-2.5%.

[0039] In another preferred embodiment of the present invention, the zinc alloy is a lithium-containing ternary alloy, such as zinc-lithium-magnesium, zinc-lithium-calcium or zinc-lithium-strontium ternary alloy, wherein the sum of the mass fractions of lithium-magnesium, lithium-calcium or lithium-strontium is not greater than 2%.

[0040] The bone tissue engineering scaffold of the present invention can be used to repair large bone defects.

[0041] The present invention has the following beneficial technical effects:

[0042] 1. With porous zinc-based metal balls as the core, it can promote osteogenic differentiation and inhibit osteoclast differentiation. While providing support, porous zinc-based metal balls will also activate osteogenic activity, promote the regeneration and ingrowth of bone tissue, and then be gradually replaced by bone tissue during the degradation process, play a bone balancing role, regulate the process of osteogenic and osteoclast differentiation, promote local new bone formation, and gradually be replaced by bone tissue to complete its biological function, and then repair large bone defects;

[0043] 2. A mesh porous scaffold made of titanium or titanium alloy is used to provide mechanical support, and further provides an internal support column of the scaffold, which significantly improves the mechanical properties of the bone repair scaffold. Even if zinc-based metal is used as the scaffold, it can provide good mechanical support in the early stage and can be applied to large bone defects in load-bearing parts;

[0044] 3. Porous β-TCP particles and porous zinc-based metal balls are mixed in a certain proportion to promote bone tissue regeneration on the basis of mechanical support, and can enrich bone marrow mesenchymal stem cells to promote bone repair.

[0045] In summary, the present invention provides a bone tissue engineering scaffold with excellent mechanical properties, which can enrich mesenchymal stem cells and promote bone repair, thereby achieving the therapeutic effect of repairing large bone defects.

[0046] The concept, specific structure and technical effects of the present invention will be further described below in conjunction with the accompanying drawings to fully understand the purpose, characteristics and effects of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 It is a structural schematic diagram of a preferred embodiment of the bone tissue engineering scaffold of the present invention (without filler);

[0048] Figure 2 1 is a schematic structural diagram of another preferred embodiment of the bone tissue engineering scaffold of the present invention (without filler);

[0049] Figure 3 It is a structural schematic diagram of another preferred embodiment of the bone tissue engineering scaffold of the present invention (without filler);

[0050] Figure 4 It is a schematic diagram of the structure of the porous zinc-based metal solid sphere in the bone tissue engineering scaffold of the present invention;

[0051] Figure 5 It is a schematic diagram of the structure of porous zinc-based metal fluffy balls in the bone tissue engineering scaffold of the present invention;

[0052] Figure 6 Schematic diagram of β-TCP particles of the bone tissue engineering scaffold of the present invention, a is a large-size particle, b is a medium-size particle, and c is a small-size particle. DETAILED DESCRIPTION

[0053] Example 1

[0054] A preferred structure of the bone tissue engineering scaffold of the present invention is as follows Figure 1As shown, its grid-like support 11 is cylindrical, with a diameter of 1-5cm and a height of 2-10cm. There are four support columns 12, which are also cylindrical, inside the support, with a diameter of 0.3-0.8mm, more preferably 0.4-0.6mm. The positions of the support columns can be symmetrically arranged or arbitrarily arranged. The grid 13 of the cylindrical support is square in shape, and the diagonal length of the grid is 0.5-2mm, and its size is preferably such that the porous zinc-based metal balls and β-TCP particles will not fall out. According to actual needs, the internal support column 12 in the present embodiment may also be absent. Further, the hollow grid-like support 11 and its internal support column 12 can be made of pure titanium or titanium alloy with excellent mechanical properties, but can also be made of degradable zinc-based metal materials or other degradable metal materials as needed.

[0055] In addition to squares, grids can also be diamond or circular. Figure 2 The structure of another preferred embodiment of the present invention is shown, the support 21 is also cylindrical, but the grid 23 thereon is circular in shape, and the diameter of the circle is 0.5-2 mm.

[0056] Figure 3 The embodiment of the bone tissue engineering scaffold of the present invention is shown in which the outer shape is a sphere 31, and three support columns 32 are arranged inside the sphere, one of which passes through the center of the sphere, and the other two are arranged on both sides in a non-parallel manner, and the shape of the grid 33 is also square.

[0057] The bracket of the embodiment is filled with porous zinc-based metal balls, one form of which is a solid ball with a plurality of holes and grooves on the surface (such as Figure 4 The preparation method is to first make zinc-based metal into solid metal balls 4 with different diameters, and then use laser burning method to burn holes 41 on the zinc-based metal balls 4. The diameter of the holes is preferably 0.1-0.3 mm, the porosity is preferably 60%-90%, and the particle size of the porous zinc-based solid metal balls is preferably 0.5-5 mm. Another form of the metal ball is a porous fluffy ball rolled from zinc-based metal wire (such as Figure 5 As shown), the diameter of the metal wire is 0.1-0.3mm, and the preparation method is: firstly, the zinc-based metal is drawn into a filament with a diameter of 0.1-0.3mm, and then rolled into wire balls of different sizes, and the particle size of the porous zinc-based fluffy metal ball is preferably 2-8mm. The purpose of preparing the zinc-based metal ball into a porous form is to promote the growth of bone cells, increase the surface area of ​​the metal ball, and promote the release of zinc ions, thereby accelerating its degradation rate. In addition, the scaffold filler can also include β-TCP particles, which can be commercially available products (such as Figure 6As shown), it can also be prepared by itself. Those skilled in the art know that the β-TCP particles themselves contain small pores, the porosity is preferably 60%-90%, the pore size is less than 500μm, preferably about 200μm, and the ratio of the number of β-TCP particles to the porous zinc-based metal balls is preferably 6:4-4:6.

[0058] The zinc-based metal refers to pure zinc or a zinc alloy containing more than 90% zinc by mass. The optimal solution is that the particle size in the scaffold is not uniform, but distributed in a certain gradient; the large particle size accounts for 30%-50%, the medium particle size accounts for 20%-40%, and the small particle size accounts for 20%-40%. The filler mixed in the above proportion can better exert its biological function, bidirectionally regulate osteoblastic and osteoclast behaviors, and significantly improve the mechanical properties of the bone repair scaffold on the basis of maintaining the enrichment of bone marrow mesenchymal stem cells to promote bone repair.

[0059] Example 2

[0060] For a large femoral bone defect of about 5 cm in length, a cylindrical mesh stent was first designed according to the morphology of the bone defect. TC4 titanium alloy was used as the raw material to prepare the outer stent and internal support column. The stent was designed to be cylindrical with a diameter of 3.5 cm and a height of 5 cm. The grid holes of the stent were designed to be square or diamond-shaped with a long diameter of 0.5 mm, or the grid holes were designed to be circular with a diameter of 0.5 mm, and 4 support columns with a diameter of 0.5 mm were arranged inside. Then, a Zn-1Sr alloy (Sr1wt.%, ultimate tensile strength UTS=160MPa, yield strength YS=120MPa, elongation>30%) was selected to prepare porous zinc-based solid metal balls, the diameter of the metal balls varied from 0.5 to 5mm, and a hole groove with a diameter of 0.2mm and a porosity of 60%-90% was punched on the Zn-1Sr metal balls by laser ablation. Commercially available β-TCP particles (particle size 0.5-5mm, porosity of about 60%-90%, pore size 200μm) were selected. β-TCP particles and degradable zinc-based metal balls were mixed in a ratio of 5:5, and then particles of different sizes were filled into the stent in the following proportions:

[0061] Large particle size 3.5-5mm accounts for 50%;

[0062] Medium particle size 1.0-3.5mm accounts for 30%;

[0063] Small particles with a diameter less than 1.0 mm account for 20%.

[0064] After complete filling, the scaffold is placed in the bone defect and firmly fixed with steel plates and screws. The titanium alloy support scaffold with excellent mechanical properties provides mechanical support, and the β-TCP particles and Zn-1Sr metal balls filled in it gradually degrade, playing the role of enriching stem cells, promoting their osteogenic differentiation, accelerating the bone repair process, and thus accelerating the repair of bone defects.

[0065] Example 3

[0066] For a patient who underwent proximal humeral tumor resection, a spherical bone defect with a diameter of about 3 cm remained after the operation. First, a quasi-spherical mesh stent was designed according to the morphology of the bone defect. The outer stent and the inner support column were prepared using Zn-0.8Li-0.1Mg alloy (Li 0.8wt.%, Mg 0.1wt.%, UTS = 680MPa, YS = 540MPa, elongation 10%) as raw materials. The size of the stent was designed based on the shape of the bone defect. The stent was designed as a quasi-spherical stent with a diameter of 3 cm. The stent grid holes were designed to be square or diamond-shaped with a long diameter of 0.5 mm, or the grid holes were designed to be circular with a diameter of 0.5 mm. Three support columns with a diameter of 0.5 mm were set inside. Then, Zn-0.8Mg alloy (Mg 0.8wt.%, UTS = 370MPa, YS = 300MPa, elongation 10%) was selected to prepare zinc-based metal balls (diameters ranging from 0.5 to 5 mm). Use laser ablation to punch holes on Zn-0.8Mg metal balls with a diameter of 0.2 mm and a porosity of 60%-90%. Select commercially available β-TCP particles (particle size 0.5-5 mm, porosity of about 60%-90%, pore size 200 μm). Mix β-TCP particles and degradable zinc-based metal balls in a ratio of 6:4, and then fill the scaffold with particles of different sizes in the following proportions:

[0067] Large particle size 3.5-5mm accounts for 50%;

[0068] Medium particle size 1.0-3.5mm accounts for 30%;

[0069] Small particles with a diameter less than 1.0 mm account for 20%.

[0070] After the scaffold is filled with β-TCP particles and zinc-based metal balls, it is placed in the bone defect. The scaffold is made of a degradable zinc-based alloy with excellent mechanical properties to provide mechanical support. The β-TCP particles and Zn-0.8Mg metal balls with excellent osteogenic properties gradually degrade after being placed in the body, playing the role of enriching stem cells, promoting osteogenesis, accelerating the bone repair process, and then repairing the bone defect.

[0071] Example 4

[0072] For a large segment bone defect of the femoral shaft of about 5 cm in length, a cylindrical mesh stent is first designed according to the shape of the bone defect. The outer layer stent is prepared using TC4 titanium alloy as the raw material. The stent is designed to be cylindrical with a diameter of 3.5 cm and a height of 5 cm. The mesh holes of the stent are designed to be square or diamond-shaped with a long diameter of 2 mm, or the mesh holes are designed to be circular with a diameter of 2 mm. Then, Zn-1Sr alloy (Sr1wt.%, UTS=160MPa, YS=120MPa, elongation>30%) is selected to prepare porous zinc-based solid metal balls. The particle size of the metal balls varies from 2 to 5 mm. The Zn-1Sr metal balls are punched with a laser ablation method. The diameter is 0.2 mm and the porosity is 60%-90%. Fill the stent according to the following proportions:

[0073] Large particle size 4-5mm accounts for 50%;

[0074] Medium particle size 3-4mm accounts for 30%;

[0075] Small particle size 2-3mm accounts for 20%.

[0076] After complete filling, the scaffold is placed in the bone defect and firmly fixed with steel plates and screws, so that it can provide mechanical support while playing a bone balancing role, promoting the osteogenesis process, inhibiting osteoclast activity, and thus promoting the repair of bone defects.

[0077] Example 5

[0078] For a 4cm long bone defect at the distal end of the radius. First, a spherical mesh stent was designed according to the morphology of the bone defect. The outer layer stent was prepared with Zn-0.8Li-0.1Mg alloy (Li0.8wt.%, Mg0.1wt.%, UTS=680MPa, YS=540MPa, elongation 10%) as the raw material. The size of the stent was designed based on the shape of the bone defect. The stent was designed as a cylindrical stent with a diameter of 2cm and a height of 4cm. Then, Zn-1Mn alloy (Mn1wt.%, UTS=200MPa, YS=160MPa, elongation>80%) was used to prepare porous zinc-based solid metal balls, and the particle size of the metal balls varied from 2-5mm. A hole groove was punched on the Zn-1Mn metal ball by laser ablation, with a diameter of 0.2mm and a porosity of 60%-90%. Metal balls of different sizes were filled into the stent according to the following proportions:

[0079] Large particle size 4-5mm accounts for 50%;

[0080] Medium particle size 3-4mm accounts for 30%;

[0081] Small particle size 2-3mm accounts for 20%.

[0082] After complete filling, the scaffold is placed in the bone defect and firmly fixed with steel plates and screws, so that it can provide mechanical support while playing a bone balancing role, promoting the osteogenesis process, inhibiting osteoclast activity, and thus promoting the repair of bone defects.

[0083] Example 6

[0084] For a large femoral bone defect of about 5 cm in length, a cylindrical mesh stent is first designed according to the morphology of the bone defect, and the outer layer stent is prepared using Zn-0.8Li-0.1Ca alloy (Li0.8wt.%, Ca0.1wt.%, UTS=560MPa, YS=300MPa, elongation>30%) as the raw material. The stent is designed to be cylindrical with a diameter of 3.5cm and a height of 5cm. The mesh holes of the stent are designed to be square or diamond-shaped with a long diameter of 2mm, or the mesh holes are designed to be circular with a diameter of 2mm. Then, Zn-1Mn alloy (Mn1wt.%, UTS=160MPa, YS=120MPa, elongation>80%) is selected to prepare porous zinc-based metal fluffy balls. The Zn-1Mn alloy is first drawn into filaments with a diameter of 0.2mm, and then curled into silk balls of different sizes (such as Figure 5 Fill the bracket in the following proportions:

[0085] Large particle size > 5 mm accounts for 50%;

[0086] Medium particle size 3-5mm accounts for 30%;

[0087] Small particle size <3 mm accounts for 20%.

[0088] After the stent is filled, it is placed in the bone defect and fixed firmly with steel plates and screws. In the early stage, the stent can provide mechanical support, and then gradually degrades to release Zn 2+ , Li + , Ca 2+ , Mn 2+ , playing a role in promoting osteogenesis. As the scaffold slowly degrades, new bone tissue gradually fills the bone defect, ultimately achieving the effect of repairing large bone defects.

[0089] Example 7

[0090] For a 3 cm long bone defect at the distal end of the radius. First, a spherical porous scaffold with a diameter of about 3 cm was designed according to the morphology of the bone defect. The outer layer of the scaffold was prepared using Zn-0.8Li-0.8Mg alloy (Li 0.8wt.%, Mg 0.8wt.%, UTS=503MPa, YS=380MPa, elongation>30%) as the raw material. The size of the scaffold was designed based on the morphology of the bone defect. Then, Zn-2Cu alloy (Cu 2.0wt.%, UTS=270MPa, YS=240MPa, elongation>40%) was selected to prepare porous zinc-based metal fluffy balls. The Zn-2Cu alloy was first drawn into filaments with a diameter of 0.2 mm, and then curled into silk balls of different sizes (such as Figure 4 Place the wire balls into the bracket in the following proportions:

[0091] Large particle size > 5 mm accounts for 50%;

[0092] Medium particle size 3-4mm accounts for 30%;

[0093] Small particle size 2-3mm accounts for 20%.

[0094] After the spherical scaffold is prepared and filled, it is placed in the bone defect. After placement, it slowly degrades in the body and releases Zn 2+ , Li + Mg 2+ , Cu 2+ , playing a role in promoting osteogenesis. As the scaffold slowly degrades, new bone tissue gradually fills the bone defect, ultimately achieving the effect of repairing the bone defect.

[0095] Example 8

[0096] The electrochemical properties and corrosion properties of the zinc-based alloys used in the present invention are tested according to the following standard procedures:

[0097] (1) Electrochemical test

[0098] The tests were performed in Hank's solution at room temperature using an electrochemical workstation (Autolab, Metrohm, Switzerland). A three-electrode system of platinum electrode-saturated calomel electrode (SCE) was used for electrochemical testing. Each sample was monitored for 5400 seconds for open-circuit potential (OCP). Electrochemical impedance spectroscopy (EIS) was performed at 10 mV and a measurement frequency of 10 5 to 10 -2Hz. Potentiodynamic polarization test was then performed at a rate of 1 mV / s with a test area of ​​0.2826 cm 2 (φ6mm). Each sample group was measured at least five times. The corrosion parameters of the negative and positive parts of the polarization curves were analyzed by Linearfit and Tafel extrapolation methods, including open circuit potential (OCP), corrosion potential (E corr ) and corrosion current density (i corr ).

[0099] 1.2 Immersion experiment

[0100] The immersion test was carried out in Hank's solution at 37°C. The pH value of the solution was recorded by a pH meter (MettlerFiveEasy pH FE20K) at different time points during the immersion. After removing the corrosion products, the weight loss of the sample was measured on an electronic balance (XS105, METTLERTOLERDO) with a measurement sensitivity of 0.1 mg, and an average of five measurements were performed for each group. The in vitro corrosion rate was calculated according to the following formula: C = Δm / ρAt, where C is the corrosion rate in mm / year, Δm is the weight loss, ρ is the density of the material, A is the surface area of ​​the initial immersion, and t is the implantation time.

[0101] Some test results are shown in Table 1.

[0102] Table 1 Electrochemical parameters of pure zinc and zinc alloys in SBF solution (37±0.2℃)

[0103]

[0104]

[0105] Note: The numbers in brackets are standard deviations

[0106] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A bone tissue engineering scaffold, characterized in that: The invention comprises a hollow grid-shaped support and porous zinc-based metal balls filled therein, wherein the porous zinc-based metal balls are placed in the hollow grid-shaped support and the size of the grid prevents the balls from falling out; the hollow grid-shaped support is made of pure titanium or titanium alloy, or of a degradable zinc-based metal; the zinc-based metal refers to pure zinc or a zinc alloy containing zinc of more than 90% by mass; the hollow grid-shaped support also has an internal support column; the porous zinc-based metal balls are solid balls with a plurality of holes and grooves on the surface or porous fluffy balls rolled from degradable zinc-based metal wires, and the size ratio of the porous zinc-based metal balls is: Large particle size accounts for 30%-50%; Medium particle size accounts for 20%-40%; Small particle size accounts for 20%-40%; When the porous zinc-based metal ball is a porous solid ball, the large particle size is greater than 3.5 mm, the medium particle size is 1.0-3.5 mm, and the small particle size is less than 1.0 mm; or the large particle size is greater than 4 mm, the medium particle size is 2-4 mm, and the small particle size is less than 2 mm; when the porous zinc-based metal ball is a porous fluffy ball, the large particle size is greater than 5 mm, the medium particle size is 3-5 mm, and the small particle size is less than 3 mm.

2. The bone tissue engineering scaffold according to claim 1, characterized in that: The particle size of the solid sphere with a plurality of holes and grooves on the surface is 0.5-5 mm, the holes and grooves are circular, the diameter thereof is 0.1-0.3 mm, and the porosity is 60%-90%.

3. The bone tissue engineering scaffold according to claim 1, characterized in that: The particle size of the porous fluffy balls is 2-8 mm.

4. The bone tissue engineering scaffold according to claim 1, characterized in that: The hollow grid-shaped scaffold is also filled with β-TCP particles.

5. The bone tissue engineering scaffold according to claim 4, characterized in that: The β-TCP particles have a particle size of 0.5-5 mm, a porosity of 60%-90%, and a pore size of less than 500 μm.

6. The bone tissue engineering scaffold according to claim 4, characterized in that: The ratio of the β-TCP particles to the porous zinc-based metal spheres is 6:4-4:

6.

7. The bone tissue engineering scaffold according to claim 4, characterized in that: The size ratio of the porous zinc-based metal spheres and the β-TCP particles is: Large particle size accounts for 30%-50%; Medium particle size accounts for 20%-40%; Small particle size accounts for 20%-40%; The large particle size is greater than 3.5 mm, the medium particle size is 1.0-3.5 mm, and the small particle size is less than 1.0 mm.

Citation Information

Patent Citations

  • Compound porous beta-TCP (tertiary calcium phosphate) titanium alloy human astragal support bar and preparation method thereof

    CN102764888A

  • Method for preparing porous bone scaffold by laser and increasing performance by adding zinc oxide

    CN103845762A

  • Degradable open-cell porous zinc / zinc alloy biomaterial and preparation method thereof

    CN104258458A

  • Bioresorbable Stent

    US20150306282A1